Evaluasi Sekolah dan Madrasah Melalui Sistem Akreditasi dalam Kebijakan Pendidikan di Indonesia - Puspa Yuli Astuti; Fery Diantoro (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2021)
Improving the quality of schools/madrasahs is carried out by means of guidance by the Education Quality Assurance Institution. After conducting quality development, it is necessary to carry out an evaluation using an accreditation system that has been regulated in education policy in Indonesia. Evaluation of schools/madrasahs is very important because it will have an impact on the quality of education and subsequent education policy makers. Therefore, this paper specifically aims to describe the evaluation of schools/madrasahs through the accreditation system. The method used in this paper uses a qualitative research obtained from the literature study. While the theory used in this paper is descriptive analysis. Regarding the results obtained from this paper is a description of the mechanism of the accreditation system in evaluating schools/madrasas as a form of improving the quality of schools/madrasas. Assessment and evaluation activities are carried out based on predetermined criteria and refer to the National Education Standards. The accuracy of the results of the evaluation of schools/madrasahs has contributed to the government as an effort to improve the quality of education and the determination of further education policies.